Enhancing the efficiency of polypyrrole-dodecylbenzene sulfonic acid in-tube solid-phase microextraction coating for analysis of nitrogen-containing pesticides in water environments - Ma, Rong; Yu, Shuangshuang; Li, Yafang; Lin, Yan; Ma, Xiaodong (Frontiers in Environmental Science, 2024)
Background: With the growing use of nitrogen-containing pesticides in agriculture, their residues in the environment have raised significant public health concerns. Objective: This study aimed to develop a novel PPy-DBSA/IT-SPME coating to enhance the detection efficiency of polar nitrogen-containing pesticides in water matrices. Methods: The preparation conditions were optimized, including pyrrole concentration at 7.0 mol/L, DBSA concentration at 0.014 mol/L, oxidant concentration at 0.35 mol/L, and a coating cycle repeated 10 times. High-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) was employed for detection. Results: The novel coating effectively adsorbed 19 different categories of polar nitrogen-containing pesticides, including sulfonylureas, triazolopyrimidines, diphenyl ether herbicides, benzoylurea insecticides, and phenylurea herbicides, with unadsorbed rates below 10%. The analytical method achieved an average recovery rate of 61.92% to 115.21%, with an RSD below 5.0%. Detection and quantification limits ranged from 0.012 to 0.524 μg/L and 0.127 to 5.243 μg/L, respectively. Conclusion: The developed method is green, efficient, simple, and cost-effective. It offers an environmentally friendly and user-friendly approach for the detection of polar nitrogen-containing pesticide residues, demonstrating good recovery and precision. This method holds potential for wide application in environmental monitoring and food safety.